2017
DOI: 10.1093/hmg/ddx214
|View full text |Cite
|
Sign up to set email alerts
|

TFEB activation restores migration ability to Tsc1-deficient adult neural stem/progenitor cells

Abstract: Tuberous sclerosis complex (TSC) is an autosomal dominant genetic disorder caused by mutations in either of two genes, TSC1 or TSC2, resulting in the constitutive activation of the mammalian target of rapamycin complex 1 (mTORC1). mTOR inhibitors are now considered the treatment of choice for TSC disease. A major pathological feature of TSC is the development of subependymal giant cell astrocytomas (SEGAs) in the brain. Nowadays, it is thought that SEGAs could be a consequence of aberrant aggregation and migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Loss of TSC1/TSC2/TBC1D7 complex activity is related to mTORC1 hyperactivation, which characterizes TSC patients’ tissues, inducing several abnormalities in numerous cell biochemical processes such as the activation of transcription, translation and inhibition of autophagy. In accordance with this, numerous studies have revealed upregulation of mTORC1 in cellular and animal models of TSC and strongly indicated mTORC1 activation as the molecular bases of TSC pathology [ 66 , 67 , 68 , 69 ]. It is worth noting that the degree of mTORC1 activation correlates well with the severity of pathological symptom [ 70 ].…”
Section: Mtorc1 Signaling Pathway and Disease: The Tuberous Scleromentioning
confidence: 59%
See 1 more Smart Citation
“…Loss of TSC1/TSC2/TBC1D7 complex activity is related to mTORC1 hyperactivation, which characterizes TSC patients’ tissues, inducing several abnormalities in numerous cell biochemical processes such as the activation of transcription, translation and inhibition of autophagy. In accordance with this, numerous studies have revealed upregulation of mTORC1 in cellular and animal models of TSC and strongly indicated mTORC1 activation as the molecular bases of TSC pathology [ 66 , 67 , 68 , 69 ]. It is worth noting that the degree of mTORC1 activation correlates well with the severity of pathological symptom [ 70 ].…”
Section: Mtorc1 Signaling Pathway and Disease: The Tuberous Scleromentioning
confidence: 59%
“…Recently, we demonstrate that TFEB activation restores Tsc1 -deficent neural stem/progenitor cell migration. In this work, we suggested TFEB as a druggable protein target for SEGAs therapy that can be used for an mTOR-independent approach [ 69 ].…”
Section: Therapeutic Strategies For Tuberous Sclerosis Complexmentioning
confidence: 99%
“…TFEB overexpression also promotes tumorigenesis, angiogenesis, and metastasis by increasing lysosomal enzyme activity and the secretion of hydrolases into the extracellular space. By contrast, TFEB depletion reduces the migration of cancer cells . We showed that co‐treatment with vorinostat and melatonin reduced both nuclear localization and oligomerization of TFEB (Figure ), thereby inhibiting GBM tumorigenesis and tumor‐sphere formation by GSCs.…”
Section: Discussionmentioning
confidence: 85%
“…By contrast, TFEB depletion reduces the migration of cancer cells. 56 We showed that co-treatment with vorinostat and melatonin reduced both nuclear localization and oligomerization of TFEB (Figure 2), thereby inhibiting GBM tumorigenesis and tumor-sphere formation by GSCs.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, curcumin can reverse multidrug resistance of cancer cells, suggesting that it can also serve as a supplement to traditional chemotherapy [9,10]. Several lines of evidence show that curcumin exerts potent anticancer effects against a broad range of human cancer cells, including prostate, colon, breast, ovarian, lung, and liver cancers, and can induce cancer cell apoptosis, for example, in liver cancer cell lines, including but not limited to HepG2, SK-Hep-1, Hep3B, SUN449, and Huh7 cells, with low cytotoxic effects on normal cells [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%